Perlindungan Hukum terhadap Hak-Hak Korban dalam Perdagangan Manusia dari Persepektif Hak Asasi Manusia - Agus Yogik Palguna; I Nyoman Gede Sugiartha; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2021)
The crime of trafficking in persons often occurs among women and children. This case is mostly among adult women; this is due to demands (less economic) so that trafficking in persons often occurs. The government must eradicate this case and provide legal protection for victims of trafficking in persons so that women and children are not arbitrarily treated by traffickers. The type of research used is juridical normative; a study the discussion of which is based on laws and legal materials. The results of the analysis show that the criminal sanctions given to the perpetrators must be really sanctions that give a deterrent effect, so that the perpetrators do not repeat their mistakes. In addition, the existence of sanctions can reduce criminal cases of trafficking in persons against women and children, and no one treats women and children arbitrarily, and no longer makes women and children victims of trafficking in persons. So that children and women can become the next generation of the nation to be proud of themselves and others.